THE EFFECT OF SEX ON PAIN AND HAMSTRING LENGTH IN PATIENT WITH PATELLOFEMORAL PAIN - Maryam Mazidi; Hadi Sarafraz; Hussein Mazidi (Sport Scientific And Practical Aspects, 2025)
Back ground: patellofemoral pain (PFP) is pain in the retro patellar or per patellar region of the knee.Objective: to evaluate effect of gender on pain severity and hamstring length in patient with PFP Methods: this was a cross sectional study on 46 athletes with PFP. Hamstring length and pain was measured. Mean differences (T-test) and Pearson correlation coefficient was calculated.Results: Mean (standard deviation) values for popliteal angle and VAS in two group were 153.52(10.46) and 5(2.1) respectively. Discussion & Conclusion: this study did not show any association between sex. No association between the hamstring length and self reported pain severity were found. Further research is needed.